Negotiation games : applying game theory to bargaining and arbitration - Brams, Steven J. (London ; New York : Routledge, 2003)
This book covers such themes as: trade offs and game of chicken; the effects of power in the cease fire game; the use of threat power in sequential games and fallback bargaining and rational ngotiation.
Includes bibliographical references (p. 273-286) and index.
osc 17/05/13
Loans
Keywords: Negotiation; Political science; Game theory